Decades : a century of fashion - Silver, Cameron; DiLiberto, Rebecca (Bloomsbury, 2012)
Ten chapters, each devoted to the iconic looks of a decade. Includes original designer sketches and patterns and photos of rare couture as styled decades ago and today. Uncover a century of colorful history to inspire the stylish of today for years to come.
Obsahuje rejstřík
Keywords: přehledy; obrazové publikace; surveys; pictorial works; 20. století; móda -- 20. století; dějiny módy -- 20. století; dějiny odívání -- 20. století; módní návrháři -- 20. století; fashion -- 20th century; history of fashion -- 20th century; history of clothing -- 20th century; fashion designers -- 20th century